The Development of a Room Division Application Implementing an Intelligent Planning System (IPS) to Enhance Hotel Operational Performance - Ersy Ervina; Bethani Suryawardani; Guntur Prabawa; Fanni Khusnul Hanifa; Annisa Khoirul Husna (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
Businesses, regardless of size, must continuously adjust to fast-paced technological advancements to remain competitive, particularly in the hotel industry. The Room Division plays a vital role as the heart of the hotel business, serving as the frontliner. A significant number of hotels have implemented technological advancements inside their operational room divisions, particularly in the front office and housekeeping departments. However, there are only a limited number of apps that can provide automation for analyzing the effectiveness of room attendants using delegation systems. A prototype of the hotel room division application based on the Intelligent Planning System (IPS). The IPS module provides automated analysis with rapid and precise outcomes, minimizing human involvement and reducing the likelihood of human mistakes. The research is conducted by applying the Software Development Life Cycle (SDLC) with the waterfall model, which includes planning, development, testing, and implementation stages. The prototype's anticipated outcome is to serve as a viable solution, with innovative features potentially benefiting the hotel's operational room division.